The Effectiveness of Providing the Finger Hold Relaxation Technique on Pain Management in Melena Patients in the Asoka Room of Prof. Dr. Margono Soekarjo Purwokerto RSUD - Ika Dewi, Fitriana; Sumarni, Tri; Dwi Martyastuti, Ervita (Universitas Ibn Khaldun Bogor, 2024)
Melena is the release of black feces or feces caused by bleeding from the upper digestive tract (Vania, 2019). Hematemesis melena is bleeding that occurs in the upper gastrointestinal tract (SCBA) and is an emergency situation that is often encountered in every hospital in the world, including Indonesia. (Vania, 2019). The incidence of SCBA bleeding in European countries reaches 100 people per 100,000 people/year, the incidence in men is much higher than in women. The incidence increases with age (Milani, 2022). In Indonesia (70-85%) hemetemesis is caused by rupture of esophageal varices which occurs in patients with liver cirrhosis so the prognosis depends on the underlying disease. This study employs a case study methodology. One patient in the inpatient room served as the study's sample. By using the finger hold relaxation technique for three days, the researcher employed the five nursing care stages of assessment, diagnosis, intervention, implementation, and evaluation. The evaluation obtained by the patient showed a decrease in the scale of severe pain (7) to moderate pain (4). Nursing problems Acute pain related to biological injurious agents providing nursing care to Mr. D to overcome the problem of pain, one of them is the finger-hold relaxation technique.